Creating a two-way market via short selling and its potential use in the Islamic paradigm - Mohamad, Azhar (2015)
Short selling is the selling of a security that the seller does not own. In conventional finance, the ability to short is considered an important element of an efficient and complete market. For most Muslim scholars, however, short selling is deemed undesirable when read in conjunction with the Hadith “la tabi’ ma laysa ‘indaka”, which carries a verbatim meaning of “sell not what is not with you”. There are, however, alternative interpretations of this Hadith that may justify the use of covered short selling as one of the legitimate instruments in the Islamic paradigm. Covered short selling, which entails borrowing a security for the purpose of shorting it, may be used efficiently to lower asset prices, as theorized by Miller (1977). This paper discusses about the short selling mechanism and argues that short selling may be beneficial to consumers in an Islamic market as it creates a two-way market mechanism and can be used to stabilize asset prices.